La sessualità nella psicoterapia della Gestalt (GT): una scoping review - Roberta Stanzione1 , Sara Ballotti 3 , Matteo Defraia3 , Samuele Giovagnini 3 , Jgor Francesco Luceri 2 , Mariano Pizzimenti 2 , Iride Memè Susanna Pistacchio4 , Stefano Roti 3 , Enrico Moretto1 (Marp Edizioni, 2023)
Background and Objective: Gestalt Therapy (GT) is a humanistic and experiential approach that places a strong emphasis on awareness, present-moment experience, and the integration of disconnected parts of the self. Gestalt Therapy is particularly suited for exploring and understanding the complex dynamics of emotional experiences and human interactions. Within the context of psychotherapy, sexuality is a vital and intricate aspect of human experience and well-being. Therefore, there is a need to explore and evaluate the scientific literature regarding Gestalt Therapy interventions specifically addressing issues related to sexuality over the past decade. Methods: A comprehensive research strategy was developed to identify relevant scientific articles from four databases: ScienceDirect, PubMed, PsycINFO, and Google Scholar. The search strategy used a combination of keywords related to Gestalt Therapy, sexuality, interventions, and the specified time period. The study follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA-ScR) guidelines to ensure transparency, replicability, and methodological rigor. Two independent reviewers conducted the search, article selection, and data extraction. English-language papers published between 2013 and 2023 in peer-reviewed journals concerning work on sexuality in Gestalt Therapy were included. Scientific papers concerning sexuality and organic pathologies, other literature reviews, book chapters, books and essays were excluded. Results: The initial search yielded a total of 39 articles. After applying the inclusion and exclusion criteria, 6 articles were selected for full review. Data extraction involved categorizing the included articles according to study characteristics, participant demographics, intervention descriptions, and reported outcomes. A thematic analysis was conducted to identify common themes, emerging patterns, and research gaps. Conclusions: This scoping review provides an overview of the scientific literature on Gestalt Therapy interventions related to sexuality published between 2013 and 2023. The results can contribute to the existing evidence base, enhance understanding of the effectiveness and applicability of Gestalt Therapy in working with sexuality, and help identify areas requiring further research.